2023
DOI: 10.3390/ph16111532
|View full text |Cite
|
Sign up to set email alerts
|

Wound Healing Performance in a Moist Environment of Crystalline Glucose/Mannose Film as a New Dressing Material Using a Rat Model: Comparing with Medical-Grade Wound Dressing and Alginate

Celine Chia Qi Wong,
Kanako Tomura,
Osamu Yamamoto

Abstract: Although medical wound dressings produced using hydrocolloids and alginate were effective in wound healing, adhesion at the wound site and the resulting delayed healing have been a problem. As a new wound dressing material, crystalline wound dressings produced from glucose/mannose were used in this study, which aimed to clarify the properties, adhesion reduction, and wound healing performance of a new wound dressing. Crystalline glucose/mannose films were obtained via alkali treatment using the solution castin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(49 reference statements)
1
0
0
Order By: Relevance
“…In this study, to fabricate hollow glucose/mannose conduits, Na 2 CO 3 was added as an alkali to the glucose/mannose aqueous solution, which was expected to deacetylate the chains. Wong et al reported that the addition of Na 2 CO 3 promoted the polymerization of glucose/mannose and formed an insoluble film [26]. In this study, hollow conduits of glucose/mannose were found at 4-12 weeks postoperative.…”
Section: Discussionsupporting
confidence: 49%
“…In this study, to fabricate hollow glucose/mannose conduits, Na 2 CO 3 was added as an alkali to the glucose/mannose aqueous solution, which was expected to deacetylate the chains. Wong et al reported that the addition of Na 2 CO 3 promoted the polymerization of glucose/mannose and formed an insoluble film [26]. In this study, hollow conduits of glucose/mannose were found at 4-12 weeks postoperative.…”
Section: Discussionsupporting
confidence: 49%